Acute Ischemic Stroke Therapy in a Hybrid Emergency Room: An Institutional Observational Cohort Study - Ito, Yuta; Kudo, Daisuke; Fujita, Motoo; Osawa, Shin-ichiro; Nakagawa, Atsuhiro; Kushimoto, Shigeki (Journal of Endovascular Resuscitation and Trauma Management, 2023)
Background: Endovascular therapy within an appropriate time has been shown to improve neurological outcomes in patients with ischemic stroke. A hybrid emergency room is an emergency unit that can be used for resuscitation, computed tomography (CT), surgery, and angiography. Therefore, immediate CT and endovascular therapy can be performed without transfer to other rooms. We aimed to evaluate the possibility of using a hybrid emergency room to shorten the time to endovascular therapy in patients with ischemic stroke. Methods: This was a single-institutional, retrospective, and observational study. Patients with acute ischemic stroke who underwent endovascular therapy in the hybrid emergency room between May 2018 and May 2020 were included in the study. The main outcome was door-to-puncture time. The secondary outcomes were door-to-reperfusion and onset-to-puncture time. Descriptive statistics were also calculated. Outcome times were compared with those recommended by recent guidelines. Results: Twenty-seven patients were included in this analysis. The median age was 77 (69–83) years. The median National Institutes of Health Stroke Scale score on admission was 15 (10–21.25), while the median door-to-puncture, door-to-reperfusion, and onset-to-puncture times were 45 (29–63), 140 (100–170), and 120 (71–224) minutes, respectively. The door-to-puncture time was within the recommended time of 60 minutes for approximately 75% of the patients. Conclusions: The door-to-puncture time in our study was shorter than that recommended by the guidelines. Acute ischemic stroke management in a hybrid emergency room could shorten door-to-puncture time, which may contribute to improving patients’ neurological outcomes.